Analysis of received signal strength indicator (RSSI) improvements for radio network optimization / Asma' Arina Ab Azid - Ab Azid, Asma' Arina (2012)
Recent years has shown the exploitation growth of mobile subscribers and services. This project is the analysis one of the important data measurement for optimization process to stabilize the radio network for mobile provider. The data that have been analyzed in this project is received signal strength indicator for radio network. Mobile network systems operate on the principle of frequency reuse. Frequency reuse in a mobile network market gives a mobile operator the ability to offer higher radio traffic intensity. The data was taken from the company that does the radio network optimization for mobile provider. Tuning process is done to make a comparison for any improvement in the received signal strength. Drive test is done at the same route to measure the received signal strength. The route for the drive test is done for cluster of Pandan. There two different areas that will be analyze in this project that are covered by cluster of Pandan. Then received signal strength indication (RSSI) data was processed by using MATLAB version R2008a.